2017
DOI: 10.1186/s12957-017-1097-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cervical delta-shaped anastomosis and circular stapled anastomosis after esophagectomy

Abstract: BackgroundThe delta-shaped anastomosis has been reported to reduce anastomotic complications for a decade. However, little has been written comparing this technique with the circular stapler technique. The objective of this retrospective study was to assess the safety and efficacy of cervical delta-shaped anastomosis after esophagectomy.MethodsMedical records of patients with esophageal squamous cell carcinoma who underwent McKeown (three-incision) esophagectomy between September 2013 and June 2015 were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Yoshida et al performed TST in 33 patients, and the rate of anastomotic leakage reduced to 1.0%, compared with 13.3% after hand-sewn anastomosis (9). Huang et al reported a decrease of the incidence anastomotic leakage in a TS group compared to a CS group, although without significant difference (17). Our results are consistent with these previous studies.…”
Section: Ts Tst and Cssupporting
confidence: 91%
“…Yoshida et al performed TST in 33 patients, and the rate of anastomotic leakage reduced to 1.0%, compared with 13.3% after hand-sewn anastomosis (9). Huang et al reported a decrease of the incidence anastomotic leakage in a TS group compared to a CS group, although without significant difference (17). Our results are consistent with these previous studies.…”
Section: Ts Tst and Cssupporting
confidence: 91%
“…11,12,15 Additionally, a major strength of this study is the accurate comparison of anastomotic complications under objective homogenization of the gastric conduit status using ICG, which is not the case in previous comparative studies. [10][11][12][13][14][15] The CS technique has a major limitation. The anastomotic lumen is dependent on the original esophageal diameter, which leads to a high prevalence of anastomotic stricture.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the MC technique would reduce the prevalence of anastomotic stricture from 25% to 5%. 10,11,13 To detect such a difference, a power analysis using a 2-sided test for this primary endpoint showed that a total of 98 patients would be required to have 80% power with a ¼ 0.05 (2-sided). 23 The number of enrolled patients was set at 100 in consideration of loss to followup after surgery.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Although healing of intestinal anastomosis has been extensively studied, the pathophysiology and contributing factors are still only partially understood; briefly, tissue ischemia, leakage, suturing technique (i.e., the use of a circular stapler), and radiotherapy have been shown to be implicated [8]. Circular stapled anastomosis is an inverted anastomosis, clamping muscular and serosal tissues between both mucosal tissues, thereby resulting in anastomotic stenosis from associated scar formation [9]. Currently, no methods capable of completely preventing anastomotic stenosis have been established.…”
Section: Discussionmentioning
confidence: 99%